Effect of elevated temperature on the mechanical properties and microstructure of heavy-weight magnetite concrete with steel fibers. (October 2019) - Thomas, C.; Rico, J.; Tamayo, P.; Ballester, F.; Setién, J.; Polanco, J.A.
Abstract: In this study, the results of the physical and mechanical characterization of a high-density structural concrete for radiation shielding subjected to different intensities of thermal shock are analyzed. The concrete has been designed using high-density natural aggregates and steel reinforcing fibers, according to structural concrete requirements. The damage caused by high temperatures to concrete has been analyzed by residual physical, mechanical and microstructural characterization after thermal shock exposure. The analysis of the results allows us to determine the behavior and verify the integrity of the shielding concrete over the different temperature ranges.